Independence of Government Auditors: Anteceden and Consequences in Improving Audit Quality - Putri, Alsa Safina; Budisusetyo, Sasongko (JEMBA: Journal of Economics, Management, Business and Accounting, 2024)
Inspectorate internal audit is an important part of supervision and internal control in a government organization. The quality of the inspectorate's internal audit greatly influences management effectiveness and accountability in the use of public resources. Therefore, it is important to understand the factors that influence the quality of the inspectorate's internal audit. The aim of this research is to determine the influence of independence, work experience and accountability on the audit quality of internal auditors working at the Surabaya and Sidoarjo Inspectorates in 2023. The sampling technique used purposive sampling of 50 samples. The research instrument uses a questionnaire with five Likert scales to measure respondents' opinions. The analysis technique uses Structural Equation Modeling-Partial Least Square (SEM-PLS) consisting of descriptive statistical analysis and partial least square test. The results of this research show that independence, work experience and accountability have a positive effect on internal audit quality.